Swimming Knowledge and Freestyle Swimming Skills: A Correlational Study in Grade VIII at SMP Negeri 10 Jambi City - Muhammad Firdaus; Ilham Ilham; Mhd. Usni Zamzami Hasibuan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This research was motivated by observations during the School Field Practice or Praktik Lapangan Persekolahan (PLP) at SMP Negeri 10 Jambi City, which indicated that students had not yet fully understood or mastered the freestyle swimming technique. This study aimed to determine the relationship between swimming knowledge and freestyle swimming skills among eighth-grade students. this research employed A quantitative method with a correlational approach was employed. Data were collected through a questionnaire to measure knowledge and direct observation to assess skills. The research sample consisted of 50 students from classes 8D and 8E, selected using simple random sampling. The results showed that the majority of students' knowledge of freestyle swimming was in the good (54%) and very good (32%) categories. In contrast, their swimming skills were more varied: 34% were in the very good category, 28% good, 22% poor, and 16% very poor. The Pearson correlation test yielded a value of r = 0.184, which is categorized as very low. This indicates that students with good swimming knowledge do not necessarily possess adequate practical skills. In conclusion, mastering freestyle swimming requires repetitive, directed, and balanced motor practice alongside theoretical understanding. Therefore, swimming instruction should emphasize the integration of cognitive and psychomotor aspects.